Aplikasi Ragam Terjemahan dalam Teks Al-Qur’an dan Injil - Kardimin Kardimin (Mukaddimah: Jurnal Studi Islam, 2016)
Translation activity always involves two languages, namely the source language and the target language. In addition, the translation activity also can not be released with the cultural aspects, the cultural aspects of the source language and the target language cultural aspects. When these problems have been met, then the translation activity has met the basic requirements. The most important thing that must be understood in translation activities that translate activity is to transfer the message or information from the source language to the target language as closely as possible. Therefore, there is no absolute translation results are the same as the source language text. In other words, the translation results approximately equal to the source language at a certain percentage. The more expert translator, the better the translation because of this expertise covers various aspects such as skills, experience, and mastery of science translated. In particular, the religious text translator must also understand the ins and outs of religious sciences. Without mastery of disciplines according to the translated text, then the result will be very poor and likely to mislead. Another very important aspect in translating strategy in translating. The strategy here can be understood as a form of techniques, methods and tactics in doing the work of translating so as to produce translations with good quality. The quality of a good translation can be measured in parameter through readability, acceptability and high accuracy.